Static structural system identification for beam‐like structures using compatibility conditions. Issue 1 (11th July 2017) - Lei, Jun; Xu, Dong; Turmo, Jose
Summary: Due to the inevitable noise existing in the measured responses, structural system identification is often a challenging task in terms of the accuracy of the estimations. Structural system identification by the observability method, which is characterized by the analysis of null spaces, is a powerful tool to determine the observability of structural parameters. However, it did not cope well with measurement errors so far. In this paper, for the first time, functional relations among displacements, denoted by the term compatibility conditions, in beam‐like structures are derived by the observability method. Then, compatibility conditions are imposed in an optimization procedure to minimize the discrepancy between the measured response and the compatible one. The compatible response obtained by the optimization is used to obtain the final estimations of the parameters. In a simply supported bridge example, the proposed method is thoroughly evaluated regarding the number of measurements, error levels, and load cases. In an example of a continuous bridge, different load cases are used to estimate the bending stiffnesses of different zones. The accuracy and the efficacy of the proposed method are verified by the numerical results.